Automated, high-throughput serum glycoprofiling platform12. Issue 9 (1st September 2015) - Stöckmann, H.; O'Flaherty, R.; Adamczyk, B.; Saldova, R.; Rudd, P. M.
<x xml:space="preserve">Abstract</x> Automated glycoprofiling platform for serum analysis: biomarker discovery, analysis of clinical samples and biopharmaceuticals.